ANALISIS KESENJANGAN DIGITAL DALAM PEMANFAATAN SUMBER BELAJAR ELEKTRONIK DI LINGKUNGAN PERGURUAN TINGGI - Riyan Sanjaya; Maydi Aula Riski; Matin; Alisya Kharima Abdillah; Yesicha Viona Militya Munthe (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
This study analyzes the digital divide in the utilization of e-journals among students at Universitas Negeri Jakarta (UNJ). A qualitative method was employed through in-depth interviews with 45 students from various faculties. The results reveal that although access to e-journals has been provided through subscriptions to premium platforms, the actual utilization rate remains very low only 18% of students have ever used them, and 6.7% are active users. The findings identify a multidimensional digital divide, particularly in the aspects of skills (58% of students faced technical difficulties) and motivation (47% of students preferred alternative platforms). Analysis using the UTAUT theory uncovered barriers in performance expectancy, effort expectancy, social influence, and facilitating conditions. Disparities in usage were also evident across faculties, indicating the need for discipline-specific approaches. This study recommends comprehensive strategies, including simplifying technical access, integrating digital literacy into the curriculum, enhancing massive socialization, and expanding relevant collections. The implementation of these strategies is expected to support the transformation of UNJ's library services toward inclusive and empowering digital services